Peer support program (P-SUP) to strengthen self-management in patients with chronic conditions. (30th September 2020) - Giesen, L; Könnecke, H; Redaèlli, M; Simic, D; Heßbrügge, M; Vitinius, F; van der Arend, I; Graf, C; Biallas, B; Stock, S
Abstract: Background: Chronic care programmes (CCPs) ensure a standardised, evidence based and structured patient care. In Germany, CCPs are successful in improving quality of care and making care more patient-centred. Regarding self-management support, however, the programs only feature patient education and shared decisions on treatment goals. Peer support has proven to be a successful component in outpatient care to enhance self-management. The aim of this study is to support patients with type 2 diabetes and coronary artery disease in conducting successful self-management through a multimodal program. Methods: This randomized controlled trial (RCT) is set up for 27 months and will include a study population of approximately 1800 patients, beginning in summer 2020. The primary outcome (PO) is the reduction of hospital admissions. In addition to the PO, secondary outcomes include motivational and knowledge-based aspects. Furthermore, health-competitive and health-economic data will be collected. The formative evaluation will review the processes for implementation. The central element of the intervention will be peer support groups, in which the group will participate in physical activities and educational lectures on nutrition, exercise or disease related knowledge. Additionally, a specially designed online platform, personalized feedback for patients on medical outcomes from their family doctors, and regular telephone coaching to increase intrinsic motivation and activation will be provided. Results: In addition to the primary outcome (reduction of hospital admissions), increased motivation levels, improved quality of life and increased health literacy are expected. Conclusions: This project, funded by the Federal Joint Committee (establishment of statutory health insurance funds and medical providers in Germany), can serve as a blueprint for future implementations of public health approaches and accessible care models for patients with chronic conditions. Key messages: Peer support as a successful method to enhance self-management in patients with type 2 diabetes and coronary artery disease. A multimodal program, consisting of peer support groups, an online platform, personalized medical feedback and telephone coaching, aiming to improve quality of life in patients with chronic conditions.